Analisis SFC Campuran Biodiesel B35 Beraditif Imagina pada Mesin PLTD Luwuk Eksperimental Kinerja Energi - Anwar, Mohammad Syaiful; Ahmadi, Nur; Yusuf, Mirza (Quantum Teknika : Jurnal Teknik Mesin Terapan, 2026)
The use of B35 biodiesel in diesel engines often faces constraints related to performance and component durability, necessitating additives to improve fuel performance. Imagina® Dex Ultimate is an essential oil-based additive claimed to improve stability, cetane number, and lubrication properties, and to reduce deposits and corrosion. This study aims to analyze the characteristics of specific fuel consumption (SFC) in the use of B35 with the addition of Imagina additives in the Luwuk Diesel Power Plant (PLTD). The research method involved field testing on a diesel engine with a 1:1000 liters mixture ratio, mixing ±2 hours before testing, and operating the engine at three load levels (900, 700, and 500 kW). The test was carried out by comparing fuel without and with additives. The results showed that the addition of additives did not significantly reduce SFC across all load variations. At a load of 900 kW, energy production was relatively stable, with an increase of 0.07 kWh, while SFC increased by 0.0013 liters/kWh compared to the case without additives. Analysis of the fuel's physical properties shows that the density and flash point still meet B35 standards, while the FAME content is slightly above 35%. The calorific value did not increase significantly, and it even decreased by 0.18 MJ/kg in the Mitsubishi engine and by 0.06 MJ/kg in the Deutz engine. Based on these results, the use of the Imagina additive in B35 at the Luwuk Diesel Power Plant has not demonstrated technical feasibility in improving fuel consumption efficiency.